INCREASING STUDENT’S INTEREST IN LEARNING ENGLISH THROUGH CANVA APPLICATION - Fany Wahyuni; Armila Riza; Rani Autila (Politeknik Negeri Bengkalis, 2022)
Â Abstract : This study discusses students' interest in learning English subjects using the Canva application as a learning medium used by English teachers at SMA N 2 Batang Anai. This study aims to describe students' interest in learning English subjects using the Canva application as a learning medium. This type of research is descriptive qualitative research. The participants of this study were 70 students of class I majoring in science at SMA N 2 BATANG ANAI which were determined through purposive sampling technique. This instrument is in the form of observations by taking field notes and video recordings, questionnaires, and interviews. In this study, the researcher collected data by distributing questionnaires via google form and distributing questionnaires to 70 students, as well as recording student activities and conducting interviews with several students. Students' learning interest can be seen through 4 indicators, namely, Happy Feeling (students feel happy in learning), Attention (students' attention in learning), Interest (students' interest in learning) and Student Involment (students are actively involved in the learning process). From the data analysis, the writer can conclude that the use of Canva application as a teacher's media in learning media can increase students' interest in learning and based on the analysis, students' interest in using Canva application as an English learning medium is very high. Â Keywords: Canva application, Learning media, Learning in interest